2014
DOI: 10.1108/msq-10-2013-0233
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of alliance marketing program creativity on the relationship between alliance orientation and market performance in the services industry

Abstract: Purpose – The purpose of this paper is to examine the validity of the already suggested positive relationship between marketing alliance orientation and market performance in a service context, and to investigate the mediating role of alliance marketing program creativity (AMPC) in the relationship in detail. Design/methodology/approach – To empirically test the hypotheses, a mail survey was conducted among firms with experience of servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
(108 reference statements)
1
7
0
2
Order By: Relevance
“…The findings of this study also successfully support the findings of (Kang et al, 2014) that the creative marketing alliance strategy of meaningfulness and novelty has a positive impact on market performance in South Korea. This makes it clear that, marketing methods that can adapt to customer needs by implementing new creative ideas are the key to achieving business success (Im and Workman, 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings of this study also successfully support the findings of (Kang et al, 2014) that the creative marketing alliance strategy of meaningfulness and novelty has a positive impact on market performance in South Korea. This makes it clear that, marketing methods that can adapt to customer needs by implementing new creative ideas are the key to achieving business success (Im and Workman, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…The findings of (Pelsmacker et al, 2018) explains how the implementation of digital marketing will ultimately have a positive impact on hotel performance in Belgium. (Kang et al, 2014) found conclusions about the creative marketing alliance strategies meaningfulness and novelty had a positive performance on market performance in South Korea. Finally, (Dabrowski et al, 2019) found the results of the meaningfulness and novelty of the marketing program implemented by hotel managers positively affected the financial performance of hotels in Poland.…”
Section: Relation Of Novelty and Meaningfulness Of Digital Marketing On Hotel Performancementioning
confidence: 84%
“…Beberapa temuan penelitian telah mengidikasikan hubungan positif antara implementasi inovasi digital marketing hotel dan kinerja hotel. Kang et al (2014) menemukan fakta bahwa strategi pemasaran kreatif memiliki dampak positif pada kinerja hotel. Pelsmacker et al (2018) menyimpulkan bahwa implementasi strategi pemasaran digital membawa dampak positif pada kinerja hotel.…”
Section: Hubungan Implementasi Digital Marketing Dan Kinerja Hotelunclassified
“…Facing the future era of globalization, the company's dependence on the entrepreneurial orientation of its owners must be accompanied by the company's ability to formulate its strategy. Without the support of the right strategy, companies will find it difficult to survive in the midst of competition (Kang, Hur, & Kim, 2014). Starting from here, the company demands to be able to formulate a good marketing strategy.…”
Section: Introductionmentioning
confidence: 99%
“…This study intends to explain the differences in the results of previous studies. Most of the several previous studies related to entrepreneurial orientation, marketing program creativity, and marketing performance were carried out in the context of a developed western economy by making several large companies the objects of their research (Wahyuni & Sara, 2020;Kang et al (2014) and little is done in the context of developing countries, such as Indonesia. In addition, research on entrepreneurial orientation towards marketing performance is still a direct relationship without a mediating variable (Dzogbenuku & Keelson, 2019).…”
Section: Introductionmentioning
confidence: 99%